Health-related quality of life among children, adolescents, and adults with bladder exstrophy-epispadias complex: a systematic review of the literature and recommendations for future research. - Dellenmark-Blom, Michaela; Sjöström, Sofia; Abrahamsson, Kate; Holmdahl, Gundela (Quality of Life Research, 2019)
Purpose: Bladder exstrophy-epispadias complex (BEEC) is a rare spectrum of genitourinary malformations. Children risk long-term urinary and genital dysfunctions. To achieve a comprehensive understanding, this study aimed to review the literature on generic and disease-specific health-related quality of life (HRQOL) in BEEC patients, and methodologies used.Methods: A literature search was conducted in Pubmed/CINAHL/Embase/PsycINFO/Cochrane, from inception to May 2018. A meta-analysis of HRQOL in BEEC patients compared to healthy references was performed.Results: Twenty-one articles (published 1994-2018), describing HRQOL of children and adolescents (n = 5) and adults only (n = 5), or integrated age populations (n = 11), were identified (median sample size 24, loss to follow-up 43%, response rate 84%). Overall HRQOL was reduced in BEEC patients compared to healthy references in 4/4 studies. Impaired physical or general health in BEEC patients has been described in 9 articles, diminished mental health in 11, restricted social health in 10, and sexual health/functioning or body perception impairments in 13 articles. Urinary incontinence was the most common factor related to worse HRQOL (12 studies). In six studies, HRQOL was better than healthy norms. In eligible studies (n = 5), the pooled estimate of the effect of BEEC indicated worse HRQOL for children and adults (0 > effect sizes < 0.5). Thirty-six HRQOL assessments were used, none developed and validated for BEEC.Conclusions: HRQOL in BEEC patients may be negatively impacted, particularly considering mental and social HRQOL. Sexual health/functioning or body perception impairments may be present in adolescents and adults. However, HRQOL is heterogeneously assessed and subsequent findings are differently reported. Additional research is warranted and can be improved.